HUBUNGAN SUPERVISI DAN MOTIVASI DENGAN PEMBERIAN CAIRAN INFUS SESUAI SPO OLEH PERAWAT PELAKSANA - Widiawati, Susi; Apriana, Ona; Merdekawati, Diah (Jurnal Endurance, 2017)
Intravenous therapy (VI) is the therapy frequently used on medical care. More than 60% of clients treated at hospital applied the therapy.  The problem found was inappropriate standard operational procedure in applying Intravenous therapy. The purpose of this study was to know the correlation of supervision and motivation in  applying Intravenous therapy based on standard operational procedure  done by nurse at inpatient care facility of Siloam Hospital, Jambi.Populations were all nurses worked at the hospital. The samples were 51 nurses; it was a total sampling. The result of univariate analysis revealed that the number of respondents who had a good supervision was 30 nurses (58.9%). Meanwhile, the respondents having high motivation were 26 (51%), and the respondents who applied intravenous therapy based on standard operational procedure were 43 nurses (64.3%). The biavariate showed that there was a significant correlation between supervision and applying intravenous therapy based on standard operational procedure (p-value 0.034<0.05) and there was a significant correlation between motivation and applying intravenous therapy based on standard operational procedure (p-value 0.018<0.05). In summary, there was a significant correlation of supervision and motivation in  applying Intravenous therapy based on standard operational procedure  done by nurse at inpatient care facility of Siloam Hospital Jambi.